Estudos da linguagem audiovisual em animações estereoscópicas: análise da representação tridimensional nas narrativas - Sampedro, Paula Poiet (2016)
The research herein is consolidated in fantastical narratives presented in animation movies allied with deep perception exploration. Its development aims to investigate how visual resources are used in animation movies to emphasize fantastical narratives in current contexts. The focus is placed on animations made by digital three-dimensional environment and on the use of stereoscopy working as tools that influence on the composition of narrative tension. The study is based upon the animation movies "How to Train Your Dragon" (DreamWorks, 2010), "How to Train Your Dragon 2" (DreamWorks, 2014) and "Frozen" (Disney, 2013) because of the fantastical storytelling, which evaluates their relations with stereoscopy's visuality and three-dimension digital space. At first a historical background to consolidate stereoscopy and animation techniques is described, which leads to contemporary cinematographic scenery and the use of 3D modeling. Then the research is directed to the study of film narratives previously mentioned followed by an evaluation of three-digital-dimensional language and the three-dimension characters building, in addition to their physical and psychological characteristics. In the end of the study, an analysis of the use of stereoscopy alongside with the narrative, characters and settings modeling of the three movies is proposed, verifying the stereoscopic space use in scenes with different dramatic intensity and how stereoscopy contributes to these narratives.